La cappella di S. Paolo in S. Carlo ai Catinari: i Cavallerini e l’ingaggio di Mauro Fontana: Nuovi documenti per la storia di uno jus patronatus (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2025)
This paper, which is part of broader research, aims to clarify the dynamics that led the first chapel on the left side of the church of Santi Carlo e Biagio ai Catinari to obtain the ingenious design and the sumptuous marble coating of Mauro Fontana (1701-1767).    The    patrons   of    the chapel, the Cavallerini  family, were strictly bound in the iconographic program by the dedication of the altar to St. Paul. The altarpiece, which was transported from the old church of San Biagio, has been relocated several times within the new temple. Finally, it replaced the title of the ‘Beata Vergine’. By comparing two manuscripts by the Barnabite Father Francesco Valle on the state of the church in the mid-18th century, along with the documents in the appendix, the text analyses the macrophases and architecture of the chapel, on which Fontana would later insert the rich altar.